HUBUNGAN AKTIVITAS FISIK DENGAN KUALITAS TIDUR PADA LANJUT USIA - Ahmad Feri Susanto; Arif Wijaya; Faisol Roni (Universitas Pesantren Tinggi Darul Ulum, 2021)
Abstract One of the health disorders of the aged is the sleep disorder. In which makes sleep schedule be distruct and change. And this is the factor of self uncomfortable and the disturb the daily activities. The aim of this review is discovering the association of the body movement and the aged’s sleep quality. Database which used in this review is Google scholar, that is suitable with inclusion and exclusion criteria. Article was publish in range of 2015 – 2020, using nation and Internation Journals, observational and literatur review method in used, and the article were free also in PDF format. There were found ten identified journal which stated that the association of body movement and the aged’s sleep quality was significant. There is an association between the body movement and the aged’s sleep quality. Keywords: Body movement, Sleep quality, and aged.